Role of efflux pump and OprD porin expression in carbapenem resistance of Pseudomonas aeruginosa clinical isolates - Tuba Muderris; Rıza Durmaz; Birsen Ozdem; Tuba Dal; Ozlem Unaldı; Sibel Aydogan; Nevreste Celikbilek; Ziya Cibali Acıkgoz (Journal of Infection in Developing Countries)
Introduction: In recent years, the prevalence of multidrug-resistant P. aeruginosa has remarkably increased. Thus, we wanted to investigate the carbapenem resistance mechanisms and clonal relationship among 80 carbapenem-resistant P. aeruginosa strains.